Parasitic nematodes of reptiles (lizards and snakes) in the Monte Desert of Argentina - Castillo, Gabriel Natalio (2020)
Nematodes are little known in the Argentine herpetofauna. In order to increase and contribute to the knowledge of parasitism in reptiles, we studied nematodes found in three species of lizards (Aurivela longicauda, Liolaemus darwinii, and L. riojanus) and one species of snake (Philodryas trilineata) from the Monte desert of center-west Argentina. We registered generalist nematodes commonly found in reptiles, belonging to three taxa: Physaloptera sp. (larvae), Physaloptera retusa (adults) (Physalopteridae) and Parapharyngodon riojensis (Pharyngodonidae) (adults). Liolaemus darwinii had the lowest prevalence of Physaloptera sp. (larvae) (30%) and a mean intensity of 1.3±0.4 (1–2). The lizard A. longicauda had the highest parasitic diversity (2 taxa) with prevalence (50%) and mean intensity (4±3.5) of Physaloptera retusa (adults), also with prevalence (12.5%) and mean intensity (20±0) of Parapharyngodon riojensis (adults). Due to the low number of studied specimens, precise conclusions cannot be drawn for Liolaemus riojanus (n = 2) and P. trilineata (n = 1). However, because the hosts were previously fixed, the results probably may do not represent real infection patterns.The four reptile species correspond to new host records from Argentina, and the information provided contributes to the knowledge of endoparasitism in reptiles of the Argentine Monte region.